2012
DOI: 10.1186/1748-717x-7-31
|View full text |Cite
|
Sign up to set email alerts
|

Long-term biochemical results after high-dose-rate intensity modulated brachytherapy with external beam radiotherapy for high risk prostate cancer

Abstract: BackgroundBiochemical control from series in which radical prostatectomy is performed for patients with unfavorable prostate cancer and/or low dose external beam radiation therapy are given remains suboptimal.The treatment regimen of HDR brachytherapy and external beam radiotherapy is a safe and very effective treatment for patients with high risk localized prostate cancer with excellent biochemical control and low toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 36 publications
1
10
0
1
Order By: Relevance
“…In general, most HDR studies (87,97,110114), found no benefit to addition of ADT. The preliminary results of the Spanish HDR RCT reported no benefit to ADT (119).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In general, most HDR studies (87,97,110114), found no benefit to addition of ADT. The preliminary results of the Spanish HDR RCT reported no benefit to ADT (119).…”
Section: Discussionmentioning
confidence: 96%
“…Most of patients in these studies received short term ADT in order to downsize the prostate prior to brachytherapy. ADT consistently showed improved in bPFS in patients with lower BED/D90 (26,81,98,106), unfavourable IR (multiple risk factors) and majority of HR patients (55,56,88,90,9395)(97). …”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Prospective randomized trials have demonstrated the advantage of dose-escalated radiotherapy in the treatment of localized prostate cancer [1-3]. Despite the implementation of new radiotherapy technologies, such as intensity modulated radiation therapy and image guided radiation therapy, rectal toxicity has remained high, thus limiting dose escalation [4-8].…”
Section: Introductionmentioning
confidence: 99%
“…A greater number of implants seem to be correlated with a higher incidence of urethral stricture. However, the incidence of rectal bleeding is higher after a single implant with multiple fractions than after multiple implantations with a single fraction [2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Okamoto et al [16] reported that high, biologically effective doses of HDR brachytherapy plus external-beam radiotherapy (EBRT) to the rectum caused grade 2 rectal bleeding or worse.…”
Section: Introductionmentioning
confidence: 97%